Improvement of Soil Physical Properties of Cambisol Using Soil Amendment - Darusman Darusman; Devianti Devianti; Edi Husen (Graduate Program of Syiah Kuala University, 2018)
Managing dryland requires intergrated knowledges on soil, water and plants relationship in order to achieve maximum yield. Using local and unused resource is important not only in aspect of reducing pollution but low price and also affordable for farmers. Thus, using amendment from in situ resources is suggested by many experts. This amendment used is assumed it could contribute improvement physical properties of soil and result better yields. This study aimed to studi more deeply on how much of soil amendment might improve physical properties of Cambisol under dryland environment and furthermore find out the crop response to soil amendments. The research was conducted during July to Oct. 2016 at Gampong Paud, Muara Tiga District, Pidie District, Aceh Province with the altitude ± 30 m asl and slope 0-3 %. A Randomized Completely Block Design (RCBD) with two factors replicated three times was used. First factor was soil amendment consisting of 4 levels ; no amendment (control), cow manure amount 10 ton ha -1, straw compost 10 ton ha-1, and cow manure 10 ton ha -1 + compost 10 ton ha-1. The second factor was 5 varieties of peanut: Tuban, Hypoma 2, Bima, Kelinci and Gajah. The parameters observed were soil bulk density, permeability, total soil porosity, aggregate stability index, soil water holding capacity at water potential -3 and -15 bar. Results of our studies showed soil amandement improves some soil physical properties, combination amendment with variety of peanuts resulted significant effects to soil physical properties, and combination treatments mostly influenced soil physical properties at soil depth of 0 -20 cm. Addition of 10 tons ha -1 cow manure or 10 ton ha -1 straw compost is enough to improve soil physical properties